Dayahuni Bandar: hubungkaitan bentuk fizikal bandar dan dayahuni setempat - Shaharudin Idrus; Abdul Samad Hadi; Abdul Hadi Harman Shah (Universiti Kebangsaan Malaysia, 2010)
This article discusses the issue of urban livability through an analysis of urban physical morphology and its relationship to existing livability of the area. The process of urbanisation itself has been on going for some time, opening up space for people migrating to the urban areas with the hope of a better life in a clean and safe environment, culminating into local livability. The article argues that good physical form, characterised by measurable physical variables, based on structured observations, can lead to a more congenial atmosphere, lively, peaceful and safe in terms of economics, social, cultural and environmental aspects, hence the livability of the place, and subsequently leading to the creation of a sustainable city. The structured observation for the study took place at 13 locations throughout the Nilai Municipality in Negeri Sembilan, which was the testbed for the research undertaken between early 2005 to late 2008. Based on nine main characteristics and 133 sub categories, the study evaluated the livability of the local urban form. The study indicated a livable city that has undergone good physical development that enabled the residents to enjoy good quality of life in a fast changing urbanisation situation. The livability of the area indicated, conducive physical traits for all ethnic groups, open and friendly with a vibrant economy, a healthy, calm and peaceful environment free from uncertainties about personal and neighburhood safety, leading to sustainable living. Such a livable city conditions is key to the development of a sustainable nation.